Blackout - Clayton, Dhonielle; Jackson, Tiffany D.; Stone, Nic; Thomas, Angie 1988-; Woodfolk, Ashley; Yoon, Nicola 1972- (Quill Tree Books, an imprint of HarperCollinsPublishers, 2021)
"Six critically acclaimed, bestselling, and award-winning authors bring the glowing warmth and electricity of Black teen love to this interlinked novel of charming, hilarious, and heartwarming stories that shine a bright light through the dark"-- As a summer heatwave blankets New York City, the light go out. The city is thrown into confusion-- and a different kind of electricity sparks. People reveal hidden truths. Love blossoms, friendship transforms, and possibilities take flight. And their stories shine a bright light through the darkness. -- adapted from jacket